Complete Genome Sequence and Comparative Genome Analysis of Variovorax sp. Strains PAMC28711, PAMC26660, and PAMC28562 and Trehalose Metabolic Pathways in Antarctica Isolates - Prasansah Shrestha; Jayram Karmacharya; So-Ra Han; Jun Hyuck Lee; Hyun Park; Tae-Jin Oh (International Journal of Microbiology)
The complete genomes of Variovorax strains were analyzed and compared along with the genomes of Variovorax strains PAMC28711, PAMC28562, and PAMC26660, Antarctic isolates. The genomic information was collected from the NCBI database and the CAZyme database, and Prokka annotation was used to find the genes that encode for the trehalose metabolic pathway. Likewise, CAZyme annotation (dbCAN2 Meta server) was performed to predict the CAZyme family responsible for trehalose biosynthesis and degradation enzymes. Trehalose has been found to respond to osmotic stress and extreme temperatures. As a result, the study of the trehalose metabolic pathway was carried out in harsh environments such as the Antarctic, where bacteria Variovorax sp. strains PAMC28711, PAMC28562, and PAMC26660 can survive in extreme environments, such as cold temperatures. The trehalose metabolic pathway was analyzed via bioinformatics tools, such as the dbCAN2 Meta server, Prokka annotation, Multiple Sequence Alignment, ANI calculator, and PATRIC database, which helped to predict trehalose biosynthesis and degradation genes’ involvement in the complete genome of Variovorax strains. Likewise, MEGA X was used for evolutionary and conserved genes. The complete genomes of Variovorax strains PAMC28711, PAMC26660, and PAMC28562 are circular chromosomes of length (4,320,000, 7,390,000, and 4,690,000) bp, respectively, with GC content of (66.00, 66.00, and 63.70)%, respectively. The GC content of these three Variovorax strains is lower than that of the other Variovorax strains with complete genomes. Strains PAMC28711 and PAMC28562 exhibit three complete trehalose biosynthetic pathways (OtsA/OtsB, TS, and TreY/TreZ), but strain PAMC26660 only possesses one (OtsA/OtsB). Despite the fact that all three strains contain trehalose, only strain PAMC28711 has two trehalases according to CAZyme families (GH37 and GH15). Moreover, among the three Antarctica isolates, only strain PAMC28711 exhibits auxiliary activities (AAs), a CAZyme family. To date, although the Variovorax strains are studied for different purposes, the trehalose metabolic pathways in Variovorax strains have not been reported. Further, this study provides additional information regarding trehalose biosynthesis genes and degradation genes (trehalases) as one of the factors facilitating bacterial survival under extreme environments, and this enzyme has shown potential application in biotechnology fields.